1988
DOI: 10.1128/mcb.8.3.1216
|View full text |Cite
|
Sign up to set email alerts
|

Localization of replication origins in pea chloroplast DNA.

Abstract: The locations of the two replication origins in pea chloroplast DNA (ctDNA) have been mapped by electron microscopic analysis of restriction digests of supercoiled ctDNA cross-linked with trioxalen. Both origins of replication, identified as displacement loops (D-loops), were present in the 44-kilobase-pair (kbp)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 21 publications
(23 reference statements)
1
43
0
Order By: Relevance
“…This observation is surprising in the light of the fact that the in vivo mechanism [20] of ctDNA replication requires two origins to produce replicating molecules with theta structures. This discrepancy may be explained by an anomalous behaviour of the pea OriA sequence in the heterologous tobacco system.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…This observation is surprising in the light of the fact that the in vivo mechanism [20] of ctDNA replication requires two origins to produce replicating molecules with theta structures. This discrepancy may be explained by an anomalous behaviour of the pea OriA sequence in the heterologous tobacco system.…”
Section: Discussionmentioning
confidence: 55%
“…with the replicative system, observed DNA synthesis as measured by the tritium incorporation assay [20] was 5 -6-fold less compared to template molecules bearing the Ori sequences. Analysis of the denatured nascent products revealed that the template-sized strands were few in number while the majority of the products was of small molecular size.…”
Section: Kinetics Of Dna Replicationmentioning
confidence: 99%
See 3 more Smart Citations